Should the Government Sell You Goods? Evidence from the Milk Market in Mexico - Jiménez-Hernández, Diego; Seira, Enrique (Pacific Conference for Development Economics (PacDev) 2021, 2021)
We study a nationwide welfare program in Mexico in which the government, in an effort to eliminate hunger, sells milk to households at subsidized rates via a network of thousands of specialized “ration stores.” Existing in many countries, such direct-provision programs often appear puzzling to economists, as it seems unlikely that the government would have any comparative advantage over the private market in procuring and distributing milk. To understand direct provision, we develop and estimate an equilibrium model of the market, then use the model to compare this program against natural (budget-neutral) alternatives, such as milk vouchers or unrestricted cash transfers. Using rich household-level panel data and the variation generated by the staggered introduction of new government stores, we show that market power by private milk suppliers is an important concern and that government-sold and privately-sold milk are close (though imperfect) substitutes. Consequently, direct provision plays an important role in the milk market in Mexico by disciplining private-milk prices. Indeed, our results suggest that in the absence of government milk, private market prices would be 3% higher. Moreover, direct provision generates 4% more gains in consumer welfare relative to milk vouchers and 2% more relative to unrestricted cash transfers.